Childhood bacterial meningitis in Mbarara Hospital, Uganda: antimicrobial susceptibility and outcome of treatment. - Kiwanuka, Julius P; Mwanga, Juliet (African Health Sciences, 2001)
Background: The recommended antibiotic treatment of bacterial meningitis has come under scrutiny following frequent reports of in-vitro resistance by the common causative organisms to penicillin and chloramphenicol. Objective: The study recorded the causative organisms, antibiotic sensitivity patterns and outcome of treatment of bacterial meningitis in children and examined the impact of various factors on the recorded outcome. Design: This was a retrospective review of all case records of patients treated for bacterial meningitis over a one-year period. Setting: The study was set in the Paediatric wards of Mbarara University Teaching Hospital, in south western Uganda. Results: A total of 77 patients were treated. Among 56 patients with available CSF results the frequency of bacterial causes was as follows: H. influenzae 13(23.2%), coliforms 7(12.5%), uncultured Gram-negative bacilli 7(12.5%), S. pneumoniae 5(8.9%) and N. meningitidis 3(5.4%). Most Isolates tested were resistant to both penicillin and chloramphenicol, but all were sensitive to ciprofloxacin and perfloxacln. Twenty eight (36.8%) patients di@ (:l,22(28.9%) survived with sequelae and 15(19.7%) improved without sequelae. 14/18 who received perfloxacin and/or ciprofloxacin survived compared with 23/47 who did not: p=0.04). Conclusions: The high case-fatality rates and the high frequency of resistance to penicillin and chloramphenicol make a case for a review of the currently recommended antibiotic treatment of bacterial meningitis in this region. Fluoroquinolones need further evaluation as potential alternatives to chloramphenicol in the treatment of bacterial meningitis.
Keywords: Childhood bacterial meningitis; Antimicrobial susceptibility; Treatment outcome